2014
DOI: 10.1155/2014/707152
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Rare Erythrocyte Phenotypes in Morocco: A Tool to Overcome Transfusion Challenges

Abstract: The aim of this research is to search for the distribution of blood groups in all the regions of Morocco. This study, done for the first time, aimed to provide the frequency of the Rhesus system and Kell (K) in more than 55000 blood donors from nine different regions around the country. In addition, the frequency of the Cellano, Duffy, Kidd, and MNS blood antigens was searched for 500 blood donors from the Rabat's region. Frequency of blood donors with rare blood groups was characterized for the first time in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A study from Morocco, KEL1 (K) is 0.19% whereas KEL2 is 99.80% (Benahadi et al, 2014). Similar study conducted in Southern Brazil documented the frequencies as KEL*02/KEL*02: 94 (75%), KEL*01/KEL*02: 5.0%, while KEL*01/KEL*01 was 0.25% (Guelsin et al, 2011;Flôres et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…A study from Morocco, KEL1 (K) is 0.19% whereas KEL2 is 99.80% (Benahadi et al, 2014). Similar study conducted in Southern Brazil documented the frequencies as KEL*02/KEL*02: 94 (75%), KEL*01/KEL*02: 5.0%, while KEL*01/KEL*01 was 0.25% (Guelsin et al, 2011;Flôres et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…In South Africa, black population Fy(a-b-) 39% while Fya+ Fyb+ was reported to be 2% (Govender et al, 2021). In Saudi Arabia, type Fy(a-b-) was identified in 11.11% (Benahadi et al, 2014). In the Brazilian Japanese population, FY study has shown that FY * 01/FY*01(Fya+) occurrence was 59.33%, FY*01/FY*02 (Fya+ Fyb+) was 38.27% and FY*02/FY*02 (Fyb+) was 2.39% (Flôres et al, 2014;Höher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of RhD negative varies between populations: 15% in Caucasians, 3-7% in Africans, 7-8% among Black Americans, and <1% in Asians [26][27][28]. Comparing different rhesus phenotypic frequencies, one can observe similarity between populations of Morocco, (DCcee: 38.85% dccee: 8.77 %), Maghreb (DCcee: 37.55% dccee: 6.12%) and Arab Gulf (DCcee: 30.9% dccee: 7.3%) [29][30][31]. These results confirm previous studies concerning ABO system.…”
Section: Discussionmentioning
confidence: 99%